Peran Koperasi dalam Pemasaran Produk Kelapa di Era Industri 4.0 - ernoiz Antriyandarti (UNEJ e-Proceeding, 2018)
Indonesia is the largest coconut producer in Southeast Asia. The relatively cheap priceof coconut make this commodity does not provide economic incentives for coconut farmers.Therefore, cooperatives can play a significant role in increasing the value of coconut productsthrough processing coconut into products that have a high added value. This study is carried outby descriptive method through survey and observation to the location of the coconut center, wherethe production and marketing were cooperatives, namely in Purworejo Disctrict, Central Java. Theresults of the study show that cooperatives have played an important role in marketing coconutproducts through coconut manufacturing and marketing to international markets both offline andonline. Coconut farmers who are members of cooperatives get many benefits, including being ableto sell coconuts at higher prices, processing them into high value-added products (VCO, coconutoil, crystal sugar, bath soap and other cosmetic products), and marketing coconut productsthroughout the archipelago and even exporting to the international market. Cooperatives inPurworejo District have succeeded in implementing the industrial system 4.0 in the value chain ofmarketing coconut products.